Enhancement of in vivo supraspinatus tendon–to-bone healing with an alginate-chitin scaffold and rhBMP-2. Issue 1 (January 2021) - Arvinius, Camilla; Civantos, Ana; Rodríguez-Bobada, Cruz; Rojo, Francisco Javier; Pérez-Gallego, Daniel; Lopiz, Yaiza; Marco, Fernando
Abstract: Introduction: Rotator cuff disorders present a high retear rate despite advances in surgical treatment. Tissue engineering could therefore be interesting in order to try to enhance a more biological repair. RhBMP-2 is one of the most osteogenic growth factors and it also induces the formation of collagen type I. However, it has a short half-life and in order to get a more stable release over time it could be integrated in a more slowly degradable carrier, such as an alginate-chitin scaffold. The aim of this study was to investigate the role of the alginate-chitin scaffold alone and in combination with different concentrations of rhBMP-2 when applied on chronic rotator cuff lesions in a rat model. Materials and Methods: We performed an experimental study with 80 Sprague-Dawley rats, 8 months old, with a chronic rupture of the supraspinatus tendon that was repaired with a modified Mason Allen suture. A scaffold was applied over the suture and 4 groups were obtained; suture (S) only suture, double control (DC) alginate and chitin scaffold, single sample (SS) scaffold of alginate with rhBMP-2 (20 µg rhBMP-2) and chitin, double sample (DS) a scaffold containing alginate with rhBMP-2 and chitin with rhBMP-2 (40 µg rhBMP-2). Macroscopic, histological and biomechanical studies were performed at 4 months after reparation. Results: The modified Åström and Rausing's histological scale (the higher the score the worse outcome, 0 points=native tendon) was applied: S got 52 points compared to DC 30 ( p  = 0, 034), SS 22 ( p  = 0, 009) and DS 16 ( p  = 0, 010). Biomechanically the maximum load was highest in DC (63, 05 N), followed by DS (61, 60 N), SS (52, 35 N) and S (51, 08), p  = 0, 025 DS vs S. As to the elastic constant a higher value was obtained in DC (16, 65), DS (12, 55) and SS (12, 20) compared to S (9, 33), p  = 0, 009 DC vs S and 0, 034 DS vs S. Conclusions: The alginate-chitin scaffold seems to promote a more biological response after the reparation of a chronic rotator cuff lesion. Its effect is further enhanced by the addition of rhBMP-2 since the osteotendinous junction is more native-like and has better biomechanical properties.